Analysis of the effect of environmental protected areas on land-use and carbon storage in a megalopolis. (December 2021) - Hwang, Jinhoo; Choi, Yuyoung; Kim, Yoonji; No Ol, Lim; Yoo, Young-Jae; Cho, Hyo Jin; Sun, Zhemin; Jeon, Seongwoo
Highlights: The impact between protected areas and carbon storage identified by city type. Different development trends identified with restriction of protected areas. Reduction in development or appearance of development in alternative sites detected. Carbon storage affected by changes in development trends. Abstract: Carbon storage in terrestrial ecosystems plays a vital role in climate control. However, urban expansion and damage to natural areas, especially the rise of megalopolises, have affected carbon storage. To mitigate this damage, various policies have been established by international, domestic, and local governments. This study focuses on the establishment and management of environmental protection areas and analyzes their impact on carbon storage. The study targets the cities of Gyeonggi-do province, South Korea, which make up a representative megalopolis, and the effectiveness of protected areas was analyzed by typifying the cities based on the proportion of available development areas and environmentally protected areas. In this study, the SLEUTH (Slope, Land-use, Excluded Area, Urban, Transportation, Hillshade) land-use change model was used to predict future land-use changes, and carbon storage was estimated using the InVEST (Integrated Valuation of Ecosystem Services and Tradeoffs) Carbon model. When operating the model, we tested a control group scenario that only preserves the water zone, a scenario that preserves the legally protected areas, and a scenario that protects the areas with high environmental value. There are two significant effects of setting up protected areas: First, the "development inhibition effect" of reducing the development area itself. Second, the "development replacement effect" of moving development to relatively low environmental value areas. These two effects differ depending on the availability of development areas, with "development replacement effects" prominent in areas with high development availability and "development inhibition effects" predominant in areas with low development availability. Future policies for setting up and managing protected areas can be used in megalopolis in conjunction with policies focusing on securing the area of carbon sinks.